2012
DOI: 10.1597/11-151
|View full text |Cite
|
Sign up to set email alerts
|

Stereophotogrammetric Analysis of Nasolabial Morphology among Asian Malays: Influence of Age and Sex

Abstract: This study has provided a new three-dimensional database for nose and lip morphology in Malays and demonstrated patterns of variation that can be used by surgeons to make comparisons within and between different human populations and also to develop treatment plans for their patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
19
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 39 publications
3
19
1
Order By: Relevance
“…The results of this study demonstrated that the Brazilian males and females had the greatest range of the nose measurements than did the Peruvians ( Figure 1): the Brazilian females showed the narrowest and shortest noses, while the Brazilian males had the greatest measurements of nose tip protrusion than did the other groups. Other studies comparing genders already found that females, in general, exhibited thinner and shorter noses than males [12,18,19].…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…The results of this study demonstrated that the Brazilian males and females had the greatest range of the nose measurements than did the Peruvians ( Figure 1): the Brazilian females showed the narrowest and shortest noses, while the Brazilian males had the greatest measurements of nose tip protrusion than did the other groups. Other studies comparing genders already found that females, in general, exhibited thinner and shorter noses than males [12,18,19].…”
Section: Discussionmentioning
confidence: 85%
“…The 3D stereophotogrammetry is the technique most used in current studies because it enables measuring variables with image depth, e.g. : volume, and linear/angular measurements [6,9,12,[17][18][19]. Table 2 displays the studies used in this discussion and the measurements found by the authors and the comparison with those of this present study.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In Asia, Mori et al [28] scanned in 3D the nasiolabial characteristics of Japanese boys and girls aged 5 to 6 years, while Al-Khatib et al [29] studied the 3D characteristics of the nose of Malaysian adolescents aged 13 to 17 years. In Africa, Sforza et al [30,31] published reference values for more than 650 Northern Sudanese people from 4 years of age into young adulthood.…”
mentioning
confidence: 99%